2000 words to start with - May Kong (Times Centre Marshall Cavendish Education, 2003)
Times 2000 Words to Start With is a full-colour picture word book is designed to introduce words in groups, starting from words about the child$1 (Bs family, body and environment to things in other countries and space. This book is a compilation of Times 1000 Words in Pictures and Times 1000 Words in Dictionary.The 1000 vocabulary items include things and concepts within the child$1 (Bs immediate experience, such as bicycle, car and van, as well as more difficult but related words such as dump truck and container lorry. The related words have been selected not only to introduce young readers to new words but also to new things that will be useful and interesting for them to know.Every page is attractively laid out, making the book a delightful means for parents to share time with their children. The lively illustrations will provide an opportunity for children to ask and answer questions, and so stimulate further interest in learning.s